Complement Activation in Association with Markers of Neutrophil Extracellular Traps and Acute Myocardial Infarction in Stable Coronary Artery Disease. (26th March 2020) - Kluge, Karsten E.; Langseth, Miriam S.; Opstad, Trine B.; Pettersen, Alf Å.; Arnesen, Harald; Tønnessen, Theis; Seljeflot, Ingebjørg; Helseth, Ragnhild
Abstract : Complement activation and neutrophil extracellular traps (NETs) have both been suggested to drive atherosclerotic plaque progression. Although experimental studies suggest interplay between these two innate immunity components, the relevance in patients with coronary artery disease (CAD) is unclear. The aim of this study was to assess associations between complement activation and NETs in patients with stable CAD and examine the role of complement activation on clinical outcome. Blood samples from a cohort of patients with angiographically verified stable CAD (n = 1001 ) were analyzed by ELISA for the terminal complement complex (TCC) and by relative quantification for gene expression of the C5a receptor 1 (C5aR1) as markers of complement activation. As markers of NETs, dsDNA was analyzed by fluorescent nucleic acid stain and myeloperoxidase-DNA (MPO-DNA) by ELISA. Clinical outcome was defined as unstable angina, nonhemorrhagic stroke, acute myocardial infarction (MI), or death (n = 106, whereof 36 MI). Levels of TCC and C5aR1 were not significantly correlated to dsDNA (TCC: r = − 0.045, p = 0.153 ; C5aR1: r = − 0.060, p = 0.434 ) or MPO-DNA (TCC: r = 0.026, p = 0.414 ; C5aR1: r = 0.123, p = 0.107 ). When dividing TCC and C5aR1 levels into quartiles (Q), levels of MPO-DNA differed significantly across quartiles (TCC: p = 0.008, C5aR1: 0.049), while dsDNA did not (TCC: p = 0.181, C5aR1: p = 0.771 ). Patients with TCC levels in Q4 had significantly higher levels of MPO-DNA than Q1-3 (p = 0.019 ), and C5aR1 levels in Q3-4 had significantly higher levels of MPO-DNA than Q1-2 (p = 0.046 ). TCC levels did not differ between patients experiencing a clinical endpoint or not, but high levels were associated with increased risk of acute MI (OR. 1.97, 95% CI: 0.99-3.90, p = 0.053 ) during two-year follow up, also when adjusted for relevant covariates. In conclusion, TCC and C5aR1 were moderately associated with the NET marker MPO-DNA, and TCC levels were related to the risk of future MI in this cohort of patients with stable CAD.